Microtremor Measurement and Damage Investigation of Historical Timber–masonry Composite Tiered Temples in Nepal. Issue 4 (3rd April 2022) - Fujita, Kaori; Ponce, D.; Toyoda, T.; Morii, M.; Niitsu, Y.; Hanazato, T.; Subedi, J.; Shakya, M.
ABSTRACT: Microtremor measurements were performed on four historical timber–masonry composite pagodas (called tiered temples) in Kathmandu Valley. Several measurements were performed between 2009 and 2017. The Gorkha earthquake occurred on April 25, 2015, causing severe damage (collapse, inclination, uplifting of the top tier, and damage to masonry walls) to the temples being monitored. The earthquake damage was assessed, and the results were compared with the structures' fundamental vibration characteristics, determined using microtremor measurements. The temples, which were surveyed before and after the earthquake, exhibited an increase in the natural period of vibration and a stiffness loss of approximately 10%. For the four temples with multiple tiers investigated, linear idealisation of the natural period of vibration with the height of the structure is proposed. By including microtremor measurements conducted in previous studies, the natural periods of the tiered temples in Nepal were found to be distributed between 0.3 and 0.7 s.